Shock propagation and banking structure - Mariassunta Giannetti; Farzad Saidi (Sveriges Riksbank, 2017)
We conjecture that lenders' decisions to provide liquidity are affected by the extent to which they internalize negative spillovers. We show that lenders with a large share of loans outstanding in an industry provide liquidity to industries in distress when spillovers are expected to be strong, because fire sales are likely to ensue. Lenders with a large share of outstanding loans also provide liquidity to customers and suppliers of industries in distress, especially when the disruption of supply chains is expected to be costly. Our results suggest a novel channel explaining why credit concentration may favor financial stability.
Keywords: E23; E32; E44; G20; G21; L14; 330; syndicated loans; bank concentration; supply chains; fire sales; externalities